Transmedia and environmental graphic strategy in museum systems: A study of three representative museums in Lima - Rodríguez Yncio, Grisel Andrea (Eikón / Imago, 2024)
The research seeks to explain the integration of digital resources and environmental graphics in a transmedia strategy as part of the museographic narrative of museums in Lima. The hypothesis suggests that, if such integration exists, then a participatory culture will be fostered that transcends the physical space of the exhibitions. A qualitative ethnographic study method with a descriptive scope was used, in which a visual analysis of graphic and interactive resources was carried out, as well as the way in which visitors relate to them. The museums studied were the National Museum of Archeology, Anthropology and History of Peru; the Place of Memory, Tolerance and Social Inclusion; and the Lima Art Museum. In the main results, it was found that the digitization of content does not necessarily promote participation in the virtual environment. Furthermore, in physical space, users look for different stimuli with which they interact and these do not necessarily come from a screen. It is concluded that there is an incipient participatory culture that transcends the physical space of museum exhibitions, and that depends exclusively on these being formulated, according to a coherent transmedia narrative, integrating digital resources and environmental graphics.